2002
DOI: 10.1354/vp.39-6-712
|View full text |Cite
|
Sign up to set email alerts
|

Early Epithelial Invasion bySalmonella entericaSerovar Typhimurium DT104 in the Swine Ileum

Abstract: Abstract. Salmonella enterica serovar Typhimurium is an important intestinal pathogen in swine. This study was performed to document the early cellular invasion of Salmonella serovar Typhimurium in swine ileum. Ileal gut-loops were surgically prepared in ten 4-to 5-week-old mixed-breed pigs and inoculated for 0-60 minutes. Loops were harvested and prepared for both scanning and transmission electron microscopy (SEM and TEM, respectively). Preferential bacterial adherence to microfold cells (M cells) was seen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…The fragmentation and vesiculation of microvilli may be due to increases in cytoplasmic Ca 2+ concentration hich lead to the actin filaments of the microvillus core cytoskeleton to be broken into short filament as mentioned previously (Embaye et al, 1989). The ultrastructural changes was observed in the epithelial cells were probably due to the presence of many intracellular Salmonella that produced cytotoxin inside the cells, these observations is similar to that observed previously in the small intestinem of the rat infected experimentally with S. typhimurium (Naughton et al, 1996) and also with that found in the ileum of swine which infected with S. typhimurium DT104 (Meyerholz et al, 2002). The loss of microvilli reduced the intestinal absorption surface, this together with the functional deficiency and destruction of many epithelial cells, lead to decrease in the absorption and caused gastroenteritis and diarrhea.…”
Section: Discussionsupporting
confidence: 87%
“…The fragmentation and vesiculation of microvilli may be due to increases in cytoplasmic Ca 2+ concentration hich lead to the actin filaments of the microvillus core cytoskeleton to be broken into short filament as mentioned previously (Embaye et al, 1989). The ultrastructural changes was observed in the epithelial cells were probably due to the presence of many intracellular Salmonella that produced cytotoxin inside the cells, these observations is similar to that observed previously in the small intestinem of the rat infected experimentally with S. typhimurium (Naughton et al, 1996) and also with that found in the ileum of swine which infected with S. typhimurium DT104 (Meyerholz et al, 2002). The loss of microvilli reduced the intestinal absorption surface, this together with the functional deficiency and destruction of many epithelial cells, lead to decrease in the absorption and caused gastroenteritis and diarrhea.…”
Section: Discussionsupporting
confidence: 87%
“…Based on these results, it seems that the IM is at least as important as the PP as the major site of early Salmonella invasion. This enterocyte-targeted invasion of Salmonella has also been reported in experiments with calves (14), pigs (27), and rabbits (57).…”
Section: Discussionsupporting
confidence: 70%
“…This time-related pattern in bacterial invasion is similar for other strains of S. Typhimurium examined in some lines of intestinal and non-intestinal cultured epithelial cells (Francis et al, 1992;Kusters et al, 1993;Mills and Finlay, 1994). Invasion of S. Typhimurium into enterocytes is detectable as early as 5-10 min after inoculation into porcine small intestinal loops (Meyerholz and Stabel, 2002;Schauser et al, 2004). In contrast to the number of organisms recovered from gentamicin-treated cells, the total number of salmonellae recovered from cell monolayers that were not treated with the antibiotic (representing both adherent and internalized organisms) remained relatively high and increased to a lesser extent over this time interval.…”
Section: Electrical Characteristics Of Porcine Ipec J2 Epithelial Celsupporting
confidence: 76%